KEKERASAN SEKSUAL DALAM KELUARGA DAN SANKSINYA DALAM HUKUM PIDANA ISLAM - Jumarni Dalle; Samsidar S; Fahri Abdullah; Anna Rahma Syam (IAIN BONE, 2026)
Sexual violence within the family is a serious crime that often remains hidden because it occurs in a private sphere and involves perpetrators who have close relationships with the victims. This study aims to analyze sexual violence within the family as a jarīmah from the perspective of Islamic criminal law and to examine the relevance of sanctions that can be applied to protect victims and prevent similar offenses. This research employs a library research method with a normative-analytical approach through the examination of fiqh jināyah literature, Islamic criminal law theories, and contemporary studies on family-based sexual violence. The findings reveal that sexual violence within the family should not be viewed merely as a moral issue or private matter but as a criminal act that violates the objectives of Islamic law (maqāṣid al-sharī‘ah), particularly the protection of life, honor, and lineage. Contributing factors include weak religious understanding, violations of privacy and modesty boundaries, exposure to sexually explicit digital content, economic pressures, and permissive social environments. Within Islamic criminal law, ta‘zīr sanctions are considered the most appropriate mechanism due to their flexibility in allowing the state to impose proportional punishments, including harsher penalties for perpetrators who are mahram relatives or hold authority over the victims. Therefore, Islamic criminal law remains relevant in strengthening family protection through education, prevention, and effective law enforcement.